Critical Thinking in Curriculum Content: The Case of Uganda - Katende, Esther (Journal of Education and Practice, 2023)
Purpose: The purpose of this study is to explore the nature of critical thinking in the curriculum content of institutions of higher learning in Uganda. The study is based on one of the institutions of higher learning in Uganda, particularly, Makerere University Business School, as a case study of institutions of higher learning in Uganda. Methodology: The methodology used is textual analysis, where curriculum documents are analyzed for aspects of critical thinking, on the basis of the higher order facets of Bloom's Taxonomy. Findings: It is the finding of this research that to a small extent, critical thinking is prevalent in the documents of the institution of higher learning analyzed. But a lot more can be done. Unique contributor to theory, policy and practice: This study is a unique contribution to theory as it shows the application of Bloom's Taxonomy, as a theoretical framework, in relation to critical thinking in Uganda's institutions of higher learning.